2002
DOI: 10.1046/j.1365-2648.2002.02394.x
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of registered nurses' experiences with web‐based learning

Abstract: Web-based learning can be an effective mode of delivery for nursing education. Advance preparation by educational institutions, employers and prospective students is essential. Teachers, peers, technology, course design and the learning environment are key variables that influence the learners' experience and success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 19 publications
8
97
0
3
Order By: Relevance
“…Similarly, their circumstances were consistent with access challenges other women learning in online universities face (Furst-Bowe & Dittmann, 2001) and which those other nurses encounter (Atack & Rankin, 2002;Care & Udod, 2000;Home, 1998).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly, their circumstances were consistent with access challenges other women learning in online universities face (Furst-Bowe & Dittmann, 2001) and which those other nurses encounter (Atack & Rankin, 2002;Care & Udod, 2000;Home, 1998).…”
Section: Discussionsupporting
confidence: 62%
“…Home (1998) revealed that their lower income increased their vulnerability to role conflict, overload and contagion. And Atack and Rankin (2002) explained that having access to computers for course work in health care settings can be problematic.…”
Section: Situating Lpn To Bn Students As Adult Women Entering Online mentioning
confidence: 99%
“…This may indicate a voluntary response bias, due to the self-selecting nature of the study, which may mean that those who have low computer confidence choose to not participate (Deniz and Citak, 2010). Alternatively, it may simply reflect the requirements of computer competency in the target populations (DH, 2004;Atack and Rankin, 2002). The low completion rate by healthcare students may be related to the fact that the tool was made available by email link to students as optional supplementary learning, the vast majority of whom were out on practice placements during the study period and balancing academic studies with clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported elsewhere among nurses and other health care professionals working in cancer care, such as social workers, psychological and spiritual care staff, and medicine. [20,34,35] Discussion forms simulate conversations that would normally occur in person. Therefore, educators should attempt to integrate activities that foster active discussion when developing online courses.…”
Section: Discussionmentioning
confidence: 99%